2013
DOI: 10.1175/jtech-d-12-00084.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional VHF Lightning Mapping System for Winter Thunderstorms

Abstract: A three-dimensional (3D) winter lightning mapping system employing very high frequency (VHF) broadband signals was developed for continuous remote observation in winter. VHF broadband pulses radiated by leader progression are received with three discone antennas arranged in a triangle (20-30 m) and recorded on a high-speed digital oscilloscope (1.25-GHz sampling) with GPS digital timing data. The two-dimensional (2D) mapping for azimuth and elevation of the VHF radiation sources was conducted by computing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…(a), the BOLT source altitude distribution of the summer lightning has large values near altitudes of 8 km, whereas the altitude distribution of the winter lightning has large values near 2 km. This result fits well with previous studies . Morimoto et al .…”
Section: Statistical Comparison Of Winter Lightning To Summer Lightnisupporting
confidence: 93%
See 1 more Smart Citation
“…(a), the BOLT source altitude distribution of the summer lightning has large values near altitudes of 8 km, whereas the altitude distribution of the winter lightning has large values near 2 km. This result fits well with previous studies . Morimoto et al .…”
Section: Statistical Comparison Of Winter Lightning To Summer Lightnisupporting
confidence: 93%
“…Nishihashi et al . observed a single flash using the VHF locating systems in the Shonai area, which is the same region as this study, and reported that the VHF source altitude distribution peaked near 2 km for one flash, which is similar to the result in this study.…”
Section: Statistical Comparison Of Winter Lightning To Summer Lightnimentioning
confidence: 99%
“…Throughout several decades, many radio source location systems for lightning discharges have been proposed, designed, and developed in an effort to obtain 2D or 3D images of lightning discharges. VHF mappers have produced detailed images of lightning discharges [e.g., Nishihashi et al ., ] and succeeded in understanding lightning processes [ Thomas et al ., ; Edens et al ., ] and the relationship between lightning discharges and thunderstorm structure [e.g., Emersic et al ., ]. However, lightning mappers for frequencies below VHF (e.g., MF or LF band) have also received attention because of their effective approach to studying narrow bipolar events (NBEs), which are also referred to as compact intracloud discharges (CIDs) [ Smith et al ., ; Nag et al ., ; Wu et al ., ; Liu et al ., ], preliminary breakdown (PB), which is sometimes called initial breakdown [ Nag and Rakov , , ; Baharudin et al ., ; Karunarathne et al ., ], and stepped leaders [ T. Takayanagi et al ., ; Bitzer et al ., ], although lightning mappers for frequencies below VHF have been developed mainly for studying return strokes [e.g., Pinto et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The Shonai area is located on the coast of the Japan Sea. The project was designed in 2007 to investigate the finescale structure of wind gusts using two X-band Doppler radars and a network of 26 surface weather stations, to develop an automatic strong-gust detection system for railroads (Kusunoki et al, 2008;Inoue et al, 2011;Nishihashi et al, 2013). One of the most notable findings was that most of the strong wind gusts during the winter season were related to the passage of misovortices (Kusunoki et al, 2009) and tornadoes (e.g., Inoue et al, 2011), and most of these had developed over the sea and subsequently made landfall.…”
Section: Introductionmentioning
confidence: 99%